2003
DOI: 10.3136/fstr.9.35
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Anti-.ALPHA.-Amylase Components from Olive Leaf Extracts

Abstract: Olive (Olea europaea L.) is recognized as a folk medicine for diabetes in Europe. The inhibitory action of an ethanol extract of olive leaves (OEE) on the activities of human amylases was examined in vitro. OEE inhibited the activities of ␣-amylases from human saliva and pancreas with IC 50 values of 4.0 and 0.02 mg/ml, respectively. Two anti-␣-amylase components were purified from a 50% ethanol soluble fraction of OEE using Sephadex LH-20 column chromatography. One was identified as luteolin-7-O-␤ glucoside a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
80
0
5

Year Published

2006
2006
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(92 citation statements)
references
References 20 publications
7
80
0
5
Order By: Relevance
“…In this paper, we present results proving that OA is not an α-amylase inhibitor. This finding is in agreement with other published data (Hou et al, 2009;Wang et al, 2011) although there are also contradictory results supporting that OA might effectively repress this activity (Khati et al, 2013;Ali et al, 2006;Komaki et al, 2003), with quite variable IC 50 values in the range of 10 µM-2.6 mM.…”
Section: Discussionsupporting
confidence: 83%
“…In this paper, we present results proving that OA is not an α-amylase inhibitor. This finding is in agreement with other published data (Hou et al, 2009;Wang et al, 2011) although there are also contradictory results supporting that OA might effectively repress this activity (Khati et al, 2013;Ali et al, 2006;Komaki et al, 2003), with quite variable IC 50 values in the range of 10 µM-2.6 mM.…”
Section: Discussionsupporting
confidence: 83%
“…It was also reported that ble state in diabetes 9 . In fact, the inhibitory activity of oleuropein s aglycon and luteolin glucosides luteolin-7-O-β-glucoside and luteolin-4 -O-β-glucoside against pancreatic amylase were determined 8 . However, the antidiabetic effects of hydroxytyrosol component have not yet been investigated against α-glucosidase and α-amylase.…”
mentioning
confidence: 99%
“…The applicant identified two human studies (Komaki et al, 2003;de Bock et al, 2013), and three animal studies (Komaki et al, 2003;Poudyal et al, 2010;Wainstein et al, 2012) as being pertinent.…”
Section: Scientific Substantiation Of the Claimed Effectmentioning
confidence: 99%